The Influence of Digital Literacy on the Job Performance of Accountants in the Bangkok Metropolitan Area - จันทร์แก้ว ศิริวัลย์; ปรีดาศักดิ์ รัตนาภรณ์; อินทร์แก้ว สุพรรณี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to (1) examine the level of digital literacy and job performance among modern accountants in Bangkok, (2) investigate the relationship between digital literacy and job performance, and (3) analyze the influence of digital literacy components on job performance. A quantitative research design was employed. Data were collected from 180 accountants using a five-point Likert scale questionnaire. The data were analyzed using descriptive statistics, Pearson’s correlation, and multiple regression analysis. The results indicated that both digital literacy and job performance were at a high level. Digital literacy was positively correlated with job performance (r = .625, p < .01) and explained 49.7% of the variance in job performance (R² = .497). Among the dimensions of digital literacy, digital ethics and cybersecurity had the strongest predictive effect (β = .404, p < .001), followed by digital data analytics and digital technical skills. The findings highlight that digital literacy represents a strategic human capital factor that significantly enhances accountants’ job performance in the digital economy context and should be systematically developed at both organizational and professional levels.